2012
DOI: 10.1115/1.4007327
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermal Response in Encapsulated Phase Change Materials by Nanotube Attachment on Encapsulating Solid

Abstract: This paper demonstrates greatly improved specific power (W/g) for encapsulated phase change materials (EPCM) as a result of modified interface morphology. Carbon nanotubes are strongly attached to the interior walls of the graphitic foam encapsulation. Microstructure analysis using scanning electron microscopy (SEM) indicates that the wax infiltrates into the carbon nanotubes (CNT) forest and creates an intimate contact with increased interfacial area between the two phases. Specific power has been calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…CNTs offer several advantages as NP supports and several earlier studies have discussed the influence of the physical and chemical nature of various support structures on advanced applications [4]. The CNT-enhanced substrates reported by our group have proved to be useful for several applications such as nanocomposite formation [5], surface adsorption [6], cell scaffolding [7], thermal management materials [8] in addition to support for metallic NPs [9][10][11].…”
Section: Introductionmentioning
confidence: 80%
“…CNTs offer several advantages as NP supports and several earlier studies have discussed the influence of the physical and chemical nature of various support structures on advanced applications [4]. The CNT-enhanced substrates reported by our group have proved to be useful for several applications such as nanocomposite formation [5], surface adsorption [6], cell scaffolding [7], thermal management materials [8] in addition to support for metallic NPs [9][10][11].…”
Section: Introductionmentioning
confidence: 80%
“…Others have reported values of 27 W/m-K with the addition of a metallized bonding layer on the CNT array [30]. More recently, studies have reported success with growing CNT arrays on graphite substrates [2,[33][34][35]. It has also been suggested that three-dimensional structures consisting of CNTs joined perpendicular to graphite may be suitable as a high-performance TIM [2].…”
Section: Introductionmentioning
confidence: 99%